Effects of fenfluramine combined with electroacupuncture on monoamine release in periaqueductal gray of rat brain - Li Xiao-yan; Zhu Chong-bin; Chen Hai-nan; Zhu Yan-hua; Wu Gen-cheng; Xu Shao-fen (Acta Pharmacologica Sinica, 2016)
AIM: To study the changes of monoamines in ventrolatoral periaqueductal gray of rat brain before and after electroacupuncture (EA) analgesia (EAA) was enhanced by fenfluramine (Fen), a 5-hydroxytryptamine (5-HT) releaser. METHODS: Monoamines were collected by in vivo microdialysis and measured by HPLC connected with electrochemical detector. RESULTS: The level of norepinephrine (Nor) after EA was decreased (P < 0.05 vs NS group). The contents of 5-HT, 5-hydroxyindol acetic acid (5-HIAA), dopamine (DA), and homovanillic acid (HVA) in periaqueductal gray dialysate were increased (P < 0.05 vs NS group). When Fen was combined with EA, the level of 5-HT and 5-HIAA were further increased (P < 0.05 vs NS + EA group). There was no obvious change of Nor, DA, and HVA. CONCLUSION: Fen potentiating EAA may be related to further activation of serotoninergic system.